Responsible Engagement: Building a Culture of Concern - Gorski, Irena; Obeysekare, Eric; Yarnal, Careen; Mehta, Khanjan (Journal of community engagement and scholarship, 2022)
As we scale up engagement with communities around the world, how do we ensure that the foundational engagement principles of responsiveness, respect, and accessibility are never compromised? While community engagement is important and can have a dramatic positive impact, it can also result in unintended negative consequences for all stakeholders, including community members, students, faculty, and staff. At Penn State, we are developing a framework for an Engagement Review Board (ERB) to proactively educate university members about the principles and best practices of engagement, and to work with them to ensure that collaborative projects benefit all stakeholders in spirit and substance. This article summarizes the larger challenge of equitable community engagement and makes the case that there is a need for additional protection such as through an ERB. The various resources and functions that can be provided by an ERB across the life cycle of engagement projects are described. The objective is to stimulate discussion on how we can collectively develop an infrastructure—undergirded by a “culture of concern” rather than a “culture of compliance”—to strengthen and mainstream community engagement without making it more onerous to all stakeholders.